Hubungan Antara Adversity Quotient Dan Work-Study Conflict Pada Mahasiswa Yang Bekerja - Evi Oktavia; Sumedi P Nugraha (Jurnal Psikologi Integratif, 2013)
ABSTRACT The purpose of this study was to investigate to relationship between adversity quotient and work-study conflict at 97 working college students in Yogyakarta. Data was collected using Adversity Quotient Scale and Work-study Conflict Scale. Analysis data using Pearson product moment showed that adversity quotient correlates negatively with work-study conflict (r=-0,639, p